(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): How does self-coaching affect the quality of life? Two hypotheses were put forward. Hypothesis 1: The most important motivator that affects the quality of life is money? And Hypothesis 2: Do individuals need self-coaching to achieve goals? Purpose: The purpose of the research is to examine the motivators that influence the quality of life, how to help yourself to raise your quality of life to a higher level, to conduct a survey and to confirm or reject the proposed theses. Method: For the research method, I performed a quantitative method and otherwise prepared a survey in the 1KA tool. I published the survey online. Results: Two hypotheses were put forward in the research. The first hypothesis that money is the most important motivator was not confirmed. Respondents chose freedom as the most important motivator. The second hypothesis, that individuals need self-coaching in achieving the set goals, was confirmed. Respondents need self-coaching in their work to achieve the set goals. Organization: The research shows the self-coffining method, which has a benefit and a positive impact on the individual as well as the organization. Society: The theoretical part of the research described the ways in which we influence the quality of our lives and thereby indirectly influence society. Originality: I don’t think I’ve ever come across a self-quarantine and a questionnaire online. Limitations/Future Research: The research should include a larger number of respondents and a larger number of questions on the topic of quality of life.